Pengaruh Model Pembelajaran Problem Based Learning Dalam Meningkatkan Konsentrasi Belajar Matematika Siswa Ditinjau Dari Hasil Belajar Siswa - Hodijah, Putri Nur Hotim; Pratama, Deni Loviga; Aji, Handaru Baskara; Ardyansyah, Arief; Agustian (Alpatih Harapan Semesta, 2025)
The purpose of this research is to explore the impact of using the Problem Based Learning (PBL) learning method on increasing the learning concentration of madrasah tsanawiyah students in mathematics subjects, based on their learning outcomes. This research uses a Quasi Experimental Research design with Non Equivalent Control Group Design. Experimental methods were used in this research. The study results showed that the average posttest score for the experimental class was 76.80%, while for the control class it was 81.80%. The gain index (g) for the experimental class is 0.67, while for the control class it is 0.54. The results of the t test show that tcount (4.307) > Ttable (2.014), with a significance value (2-tailed) < 0.05 (0.014), indicating that the use of the PBL method has a positive and significant effect in increasing students' learning concentration at Madrsah Tsanawiyah Miftahul Hasan Wangkal, Probolinggo, East Java, in Mathematics Learning.